2015
DOI: 10.1111/jar.12160
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Child Sexual Abuse in Out‐of‐home Care: Increased Risk for Children with a Mild Intellectual Disability

Abstract: Children with a mild intellectual disability in out-of-home care have an increased risk of CSA. Adequate education and support for both children and caregivers is necessary to recognize and prevent further sexual abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 37 publications
2
42
0
5
Order By: Relevance
“…Mental retardation has been reported in 35-40% of sexually abused children (15,16). The reported underlying cause is the weakness of communication skills and more dependent characteristics of mentally retarded individuals (38). In our study, the clinical and test evaluations revealed that 19.5% of the sexually abused children had mental retardation in various levels.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Mental retardation has been reported in 35-40% of sexually abused children (15,16). The reported underlying cause is the weakness of communication skills and more dependent characteristics of mentally retarded individuals (38). In our study, the clinical and test evaluations revealed that 19.5% of the sexually abused children had mental retardation in various levels.…”
Section: Discussionmentioning
confidence: 45%
“…Children who are mentally retarded or physically handicapped, neglected and socially isolated are at higher risk for abuse (36)(37)(38). Mental retardation has been reported in 35-40% of sexually abused children (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Mağdur olmayla başlayan süreç; güçsüzlük hissi ve öfke yaratmakta, bu öfke artık güçsüz olmadığını gösterecek biçimde zarar verici davranışlara dönüşmektedir. (40,41).…”
Section: çOcuk Ya Da Ebeveynin Psikopatolojileriunclassified
“…A large body of research shows that the prevalence of abuse of children with intellectual disability (ID) is higher than that of their peers without disability (Lightfoot, Hill, & LaLiberte, ; Verdugo, Bermejo, & Fuertes, ). They are two times (Sullivan & Knutson, ), three times (Euser, Alink, Tharner, van Ikzendoorn, & Bakermans‐Kranenburg, ; Sullivan & Knutson, ) and even four times more likely to suffer some form of abuse (Barber & Delfabbro, ). It is therefore not surprising that among children in out‐of‐home care, there is a significant representation of children with ID, which some authors have estimated to be at about 10% (Hill, ; Lightfoot et al, ).…”
Section: Introductionmentioning
confidence: 99%